Relationship between self-efficacy and language proficiency: A meta-analysis. (December 2020) - Wang, Chuang; Sun, Ting
Abstract: This study aims to estimate the average effect size of the relationship between self-efficacy and language proficiency and to examine factors that moderate the relationship. A meta-analysis of the 493 effect sizes for the relationship between language learners' self-efficacy beliefs and their language proficiency from 74 published journal articles, book chapters, and dissertations revealed an average of small to medium effect size. The use of hierarchical linear models indicated 76.7% of the variance between the published works, suggesting that the effect size varies across studies. Effect sizes reported in studies with East Asian students were larger than those reported in studies with students in Western culture. Parameter estimates of fixed effects noted that the effect sizes reported from zero-order correlations inflated the effect size without consideration of the language, culture, grade-level, sample size, and data analysis procedures. This study contributes to the literature by summarizing studies from the last two decades in a systematic way and cautions researchers when interpreting effect sizes reported in the literature. Highlights: Small to medium effect sizes about the relationship between self-efficacy and language proficiency. Large proportions (77%) of the variance in effect size exists between studies. Effect sizes with East Asian students were larger than those in the Western culture. The use of Pearson correlation method inflates the effect size. Researchers are recommended to rely more on the regression slopes or loadings from structure equation models. Help students develop more accurate self-efficacy by considering cultural differences.